Floating Drug Delivery System: An Innovative Approach - verma, Anamika; Verma, Priyanka; Khinchi, M. P; Soni, S. L (Asian Journal of Pharmaceutical Research and Development, 2015)
Floating drug delivery system has been evolved as a controlled drug delivery system. Several approaches are currently being used including floating drug delivery system (FDDS) which is also known as Hydrodynamically balanced system (HBS), swelling and expanding systems, high – density systems, bioadhesive systems, modified shape systems and other delayed gastric emptying devices. Several approaches are currently utilized in the prolongation of the GRT, including floating drug delivery systems (FDDS), swelling and expanding systems, polymeric bioadhesive systems, high-density systems, modified-shape systems and other delayed gastric emptying devices. Floating dosage form can be prepared as tablets, capsules by adding suitable ingredients as well as by adding gas generating agent.